Macromol. Mater. Eng. 1/2013. Issue 1 (7th January 2013) - Sakai, Reika; John, Baiju; Okamoto, Masami; Seppälä, Jukka V.; Vaithilingam, Jayasheelan; Hussein, Husnah; Goodridge, Ruth
<x xml:space="preserve">Abstract</x> Front Cover: Tissue engineering scaffolds prepared by the polymerization of crosslinked PLA possess excellent pore connectivity, morphology, structural stability and biodegradability. These thermoset PLA scaffolds are free of bioceramics, and are suited for the repair and regeneration of bone tissues. Further details can be found in the article by R. Sakai, B. John, M. Okamoto, * J. V. Seppälä, J. Vaithilingam, H. Hussein, and R. Goodridge on page 45. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>